IMPROVING THE STUDENTS’ MOTIVATION AND SPEAKING ABILITY BY USING THEMATIC SIMULATION GAME (TSG) FOR THE FIRST SEMESTER OF MIDWIFE PROGRAM AT AKBID HUSADA GEMILANG TEMBILAHAN - Mustajib, Agus (ENGLISH JOURNAL OF INDRAGIRI, 2017)
This research is conducted to improve the students’ motivation and speaking ability by using the thematic simulation game. It also purposes to give the general description about the implementation of using the thematic simulation game in the English class and about everything happening in the class. Then, the objectives of this research are to improve the students’ motivation and speaking ability after determining the problem. The method used in this research is classroom action research. This classroom action research concerns with solving the problems by identifying them, planning, implementing the action, observing the action, and reflecting the result of the observation, and revising the plan for the following steps. The research is conducted in two cycles to the first semester students of midwife program at Akbid Husada Gemilang Tembilahan. The researcher taught speaking English using the thematic simulation game. The research data are collected by using techniques of qualitative and quantitative data collection, which include a questionnaire, observation, and test. The result of the research shows that using the thematic simulation game can improve motivation and speaking ability from the first cycle to the second cycle. It explained that the students have good interaction. The students also enjoyed their performance in acting in front of the class. Moreover, they practiced speaking through the appropriate media. In the pre-test, the students’ mean score is 52.4 as the beginning of the research and it has improved during the research. As has been explained, the lowest point was 50 and the highest point was 72 in the first cycle and the lower point was improved into 60 and the higher point was 86 in the second cycle. It means that there is also the improvement in speaking ability.